The underestimated virtues of the two-sector AK model - Gabriel Felbermayr; Omar Licandro (Johannes Kepler University of Linz, Department of Economics, 2003)
We show that the two-sector version of the AK model proposed by Rebelo (1991) can be read as an endogenous growth extension of Greenwood, Hercowitz and Krusell (1997). By confining constant returns to capital to the investment goods sector, the model generates endogenously the secular downward trend of the relative price of equipment investment and the rising real investment rate observed in US NIPA data. Whereas Jones (1995) criticizes that the one-sector model fails to reconcile the empirical facts of trending real investment rates and stationary output growth, this incompatibility vanishes in the two-sector version. Finally, a simple technological shock can reproduce the `1974' break in post World War II US data. Thus, AK-type endogenous growth models comply much better with empirical evidence, once they are augmented with a strictly concave consumption sector.
Keywords: O41; O30; 330; AK model; embodiment; endogenous growth; obsolescence; 1974; Neue Wachstumstheorie; Theorie